Mechanical and Thermal Properties of RCB Masonry Containing Three Rows of Holes - Hanquan Yuan; Lihua Zhu; Yixuan Wang; Fengjian Zhang (Advances in Materials Science and Engineering)
In order to promote and apply the structures of the recycled concrete block (RCB) masonry, the thermal and mechanical properties of the recycled concrete specimens were tested in this study. The RCB can meet load-bearing and seismic requirements and was prepared through experiments. Concurrently, the mechanical property experiment was conducted on the RCB masonry, and then its failure process and mode were discussed. In addition, a thermal property test was completed on the RCB wall, and the difference in the thermal properties of single-row hole, three-row hole, and solid blocks was analyzed by theoretical calculations. The results indicated that the mechanical properties of the RCB masonry were basically the same as those of the natural concrete block masonry, and they have good compressive stability. The calculation formulas of the compressive and shear strengths of the natural concrete block masonry are applicable to the RCB masonry. The RCB masonry containing three rows of holes owns more outstanding thermal property than natural concrete block masonry and satisfies the requirements for related codes.